HALAL COSMECEUTICAL : KUTEKS WUDLU FRIENDLY DAN TERAPI DERMATOMIKOSIS DARI EKSTRAK PACAR AIR (Impatiens balsamina L) - Angrraeni, Yunita Dwi; Mumpuni, Wanda Danis; Sutanto, Gusnul; Wijayanti, Rina (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2019)
Pacar air leaves (Impatiens balsamina L.) contains saponin which has activity as anantifungal, can inhibit the growth of Candida albicans which causes dermatomycosis. Thepurpose of this study was to determine the inhibition of Pacar air leaves (Impatiensbalsamina L.) made in gel nail polish preparations for the growth of Candida albicans.Experimental research used a sample in the form of pure nail extract and extract. Physicalpreparation tests were carried out on formula I and formula II in the form of organoleptictests, homogeneity, dispersion, adhesion and pH. The results showed that the pH test in bothformulas did not irritate the skin. The scattering power test in both formulas spread well andthe sticky strength test on both formulas could be attached to the skin in more than 1 second.The homogeneity test in both formulas showed the presence of fine and flat particles. Theinhibitory test of Pacar air extract (Impatiens balsamina) on fungal growth of Candidaalbicans using the SPSS application was significantly different. In conclusion, formula II andpure extract showed antifungal activity which could inhibit the growth of Candida albicanswhere pure extract had the greatest inhibitory power.